Carbon capture cement self-repairing agent as well as preparation method and application thereof

By using carbon capture cement self-repairing agent in cement cement rings, the problem of slow self-repairing speed is solved, rapid self-repairing of cement matrix and improved rheology performance, significantly improving the self-repairing ability of cement cement rings.

CN119591341AActive Publication Date: 2025-03-11TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411787021.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing cement cement ring self-repair technology has the problem of slow self-repair speed, which limits its application value in cementing projects.

Method used

Carbon capture cement self-repairing agent is used, which consists of aqueous epoxy resin, surfactant and tertiary amine curing agent. Through specific preparation methods and additive ratios, a self-repairing agent with excellent carbon capture performance is formed.

Benefits of technology

The self-repair speed of cement matrix has been significantly improved, the self-repair capacity has been improved by 516.3%, and it has a small impact on cement hydration, which is conducive to improving cement rheology performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591341A_ABST
    Figure CN119591341A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of well cementation cement sheath self-repairing, in particular to a carbon capture cement self-repairing agent and a preparation method and application thereof. The preparation method comprises the following steps: uniformly mixing water-borne epoxy resin, a surfactant and water to obtain an epoxy emulsion; a tertiary amine curing agent is added into the epoxy emulsion for a reaction, and a carbon capture cement self-repairing agent solution is obtained; the carbon capture cement self-repairing agent solution is subjected to freeze drying and then ground, and the carbon capture cement self-repairing agent is obtained. The obtained carbon capture cement self-repairing agent is easy to industrially prepare, is beneficial to improving the rheological property of cement paste, and can realize rapid self-repairing of a cement matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cement ring self-repairing for well cementing, and in particular to a carbon capture cement self-repairing agent and a preparation method and application thereof. Background Art

[0002] Cementing engineering is one of the important links in the exploitation of oil and gas resources, which directly determines the quality of oil and gas resource exploitation. It achieves the purpose of protecting oil and gas well casing, increasing the life of oil and gas wells and increasing oil and gas production by injecting cement slurry between the casing and the formation. However, cement-based materials are brittle. Under the influence of external loads and environmental changes, the cement matrix is ​​very easy to crack, resulting in the failure of the sealing integrity of the cement ring, which seriously threatens the safety of oil and gas resource exploitation. Considering the repair effect and cost of cement ring, self-healing technology derived from the biological field is becoming the most important solution to cement ring cracking.

[0003] Considering the high temperature and complex environment of cementing cement ring, among various self-repairing methods, self-repairing by adding crystallization promoters to stimulate the secondary hydration of unhydrated cement particles in cement to achieve crack closure has a wider range of application scenarios and better micro-crack filling effect. Gong et al. induced the formation of calcium carbonate crystals in a high concentration of carbon dioxide environment by calcium carbonate whiskers. The volume self-repair rate of cement matrix cracks added with calcium carbonate whiskers reached 55.24% after 28 days of self-repair. Peng et al. synthesized a permeable crystallization self-repairing agent CWS. The study showed that the permeability of the cement matrix added with CWS was reduced by 97.5% after 28 days of self-repair, and the strength recovery rate was 92.7%.

[0004] However, the self-repairing products generated by self-repairing mainly come from calcium carbonate produced by the carbonation of calcium hydroxide, which still has the disadvantage of slow self-repairing speed. It usually takes 14 to 28 days of self-repairing time to achieve a high self-repairing rate, which limits the application value of self-repairing in cementing engineering. Therefore, providing a new carbon capture cement self-repairing agent to accelerate the absorption of carbon dioxide by the cement matrix, promote the generation of self-repairing products, and significantly improve the self-repairing speed of the cement matrix is ​​of great significance to the field of cement ring self-repairing technology. Summary of the invention

[0005] Based on the above content, the present invention provides a carbon capture cement self-repairing agent and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention is a method for preparing a carbon capture cement self-healing agent, comprising the following steps:

[0008] Evenly mixing water-based epoxy resin, surfactant and water to obtain epoxy emulsion;

[0009] Adding a tertiary amine curing agent to the epoxy emulsion for reaction to obtain a carbon capture cement self-healing agent solution;

[0010] The carbon capture cement self-repairing agent solution is freeze-dried and then ground to obtain the carbon capture cement self-repairing agent.

[0011] The second technical solution of the present invention is a carbon capture cement self-healing agent prepared according to the above-mentioned preparation method.

[0012] The third technical solution of the present invention is the application of the carbon capture cement self-healing agent in the self-healing of cement rings in cementing.

[0013] A fourth technical solution of the present invention is a self-healing cement-based material, the raw materials of which include the carbon capture cement self-healing agent and cement.

[0014] The present invention discloses the following technical effects:

[0015] 1. The preparation method of the carbon capture cement self-healing agent of the present invention is simple and easy to realize industrial production.

[0016] 2. The carbon capture cement self-healing agent of the present invention has little effect on cement hydration and is beneficial to improving the rheological properties of cement.

[0017] 3. The carbon capture cement self-healing agent of the present invention has excellent carbon capture performance, can accelerate the generation of cement matrix self-healing products, and significantly improve the self-healing ability of the cement matrix. Compared with the blank G-grade oil well cement matrix, the improvement is 516.3%. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 The scanning electron microscope image and X-ray energy spectrum analysis image of the carbon capture cement self-healing agent prepared in Example 1 in the cement matrix, wherein (a) is a morphology image of the carbon capture cement self-healing agent in the cement matrix, (b) is a local magnified image of the carbon capture cement self-healing agent in the cement matrix, (c) is a C element distribution image, (d) is an O element distribution image, (e) is an N element distribution image, and (f) is a Ca element distribution image;

[0020] Figure 2The thermogravimetric test diagram of the carbon capture cement self-healing agent prepared in Example 1, wherein (a) is the thermogravimetric curve, and (b) is the first-order derivative curve of the thermogravimetric curve;

[0021] Figure 3 This is a carbon dioxide adsorption test diagram of the carbon capture cement self-healing agent prepared in Example 1;

[0022] Figure 4 The rheological test diagrams of the cement matrix prepared in the control example, example 1, example 2 and example 3;

[0023] Figure 5 The hydration heat release test diagram of the cement matrix prepared in the control example, example 1, example 2 and example 3;

[0024] Figure 6 The super depth of field pictures and the repair rates of the cement matrix prepared in the control example and embodiment 1 before and after repair, wherein, (a) is the super depth of field picture and the repair rate of the cement matrix prepared in embodiment 1 before repair, (b) is the super depth of field picture and the repair rate of the cement matrix prepared in embodiment 1 after 1 day of repair, (c) is the super depth of field picture and the repair rate of the cement matrix prepared in embodiment 1 after 7 days of repair, (d) is the super depth of field picture and the repair rate of the cement matrix prepared in the control example before repair, (e) is the super depth of field picture and the repair rate of the cement matrix prepared in the control example after 1 day of repair, and (f) is the super depth of field picture and the repair rate of the cement matrix prepared in the control example after 7 days of repair. DETAILED DESCRIPTION

[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0026] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0027] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0028] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0029] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0030] The first aspect of the present invention provides a method for preparing a carbon capture cement self-repairing agent, comprising the following steps:

[0031] Evenly mixing water-based epoxy resin, surfactant and water to obtain epoxy emulsion;

[0032] Adding a tertiary amine curing agent to the epoxy emulsion for reaction to obtain a carbon capture cement self-healing agent solution;

[0033] The carbon capture cement self-repairing agent solution is freeze-dried and then ground to obtain the carbon capture cement self-repairing agent.

[0034] In a preferred embodiment of the present invention, the mass fraction of the waterborne epoxy resin in the epoxy emulsion is 50.0%-60.0%; the mass fraction of the surfactant in the epoxy emulsion is 0.5%-0.6%.

[0035] In the present invention, if the amount of surfactant added to the epoxy emulsion is too high, the cost of the carbon capture cement self-healing agent will increase; if the amount of surfactant added is too low, the epoxy resin emulsion will be unstable, and the carbon capture cement self-healing agent solution will react incompletely and unevenly; if the amount of water-based epoxy resin added to the epoxy emulsion is too high, the emulsion will be unstable, the reaction will be uneven, and the tertiary amine group content will be low; if the amount of water-based epoxy resin added is too low, the yield of the carbon capture cement self-healing agent will be too low, and the cost will increase. Therefore, the present invention preferably limits the mass fraction of water-based epoxy resin and surfactant in the epoxy emulsion to the above parameter range.

[0036] In a preferred embodiment of the present invention, the waterborne epoxy resin is a waterborne modified bisphenol A epoxy resin, a waterborne modified bisphenol F epoxy resin or a waterborne modified bisphenol S epoxy resin; and the surfactant is Span-80, Span-60 or Span-85.

[0037] In a preferred embodiment of the present invention, the epoxy value of the waterborne epoxy resin is 0.41-0.51, and the average dispersed particle size in water is 4-8 μm. In a further preferred embodiment of the present invention, the epoxy value of the waterborne modified bisphenol A epoxy resin is 0.51; the epoxy value of the waterborne modified bisphenol F epoxy resin is 0.44; and the epoxy value of the waterborne modified bisphenol S epoxy resin is 0.41.

[0038] In the present invention, if the epoxy value of the water-based epoxy resin is too low, the yield of the carbon capture cement self-healing agent solution will be too low, and the thermal stability of the prepared carbon capture cement self-healing agent will be worse; if the dispersed particle size in water is too high, the carbon capture cement self-healing agent will not be evenly dispersed in the cement matrix, further deteriorating the mechanical properties of the cement matrix and failing to improve the rheological properties of the cement.

[0039] In a preferred embodiment of the present invention, the mass fraction of the tertiary amine curing agent in the epoxy emulsion is 25.0%-30.0%.

[0040] In a preferred embodiment of the present invention, the tertiary amine curing agent is dimethylaminopropylamine, 4-dimethylaminobutylamine or dimethylaminoethylamine.

[0041] In the present invention, the tertiary amine curing agent not only acts as an epoxy resin curing agent, but also provides abundant tertiary amine groups, so that the carbon capture cement self-healing agent prepared therefrom has more carbon dioxide capture sites and better self-healing effect. If other curing agents commonly used in the art such as triethylenetetramine, m-phenylenediamine, and diaminodiphenyl sulfone are used, a cross-linked structure will be formed, and a self-healing agent solution cannot be formed after curing, and it is difficult to disperse evenly in the cement paste. In addition, the nitrogen content of the carbon capture cement self-healing agent is reduced, and sufficient tertiary amine groups cannot be provided as stable carbon dioxide capture sites, and the self-healing performance is reduced.

[0042] In a preferred embodiment of the present invention, the reaction temperature is 60-80°C and the reaction time is 4-10 hours.

[0043] The present invention does not impose any particular limitation on the freeze-drying parameter settings, and conventional freeze-drying parameter settings in the art may be used.

[0044] The present invention does not impose any particular limitation on the particle size of the ground particles, and the particle size conventionally added to cement in the art may be used, such as 10-100 microns.

[0045] A second aspect of the present invention provides a carbon capture cement self-healing agent prepared according to the above-mentioned preparation method.

[0046] The third aspect of the present invention provides the use of the carbon capture cement self-healing agent in the self-healing of cement rings in cementing.

[0047] A fourth aspect of the present invention provides a self-healing cement-based material, the raw materials of which include the carbon capture cement self-healing agent and cement.

[0048] In a preferred embodiment of the present invention, the mass ratio of the carbon capture cement self-healing agent to the cement is (1-6):(99-94).

[0049] The self-repairing cement-based material has good self-repairing performance in a high-temperature carbon dioxide environment.

[0050] In some specific implementation cases of the present invention, the cement is Class G oil well cement.

[0051] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0052] The G-grade oil well cement used in the embodiments of the present invention comes from Sichuan Jiahua Enterprise Co., Ltd., and the G-grade oil well cement obtained through other channels is also applicable to the present invention.

[0053] The epoxy value of the water-based modified bisphenol A epoxy resin used in the embodiment of the present invention is 0.51, and the average dispersed particle size in water is 4.1 μm; the epoxy value of the water-based modified bisphenol F epoxy resin is 0.44, and the average dispersed particle size in water is 5.3 μm; the epoxy value of the water-based modified bisphenol S epoxy resin is 0.41, and the average dispersed particle size in water is 7.8 μm.

[0054] The test method involved in the present invention is as follows:

[0055] The carbon dioxide adsorption test method is a conventional technical means in this field and is not the focus of patent protection of the present invention, so it will not be described here; the rheological test and hydration exothermic test refer to the GB / T 19139-2012 standard.

[0056] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0057] Example 1

[0058] A method for preparing a carbon capture cement self-repairing agent, comprising the following steps:

[0059] (1) Preparation of epoxy emulsion: Mix water-based modified bisphenol A epoxy resin, Span-80 and water, and stir them evenly at 10,000 rpm to obtain epoxy emulsion; the mass fraction of the water-based modified bisphenol A epoxy resin in the epoxy emulsion is 50.0%; the mass fraction of Span-80 in the epoxy emulsion is 0.5%.

[0060] (2) Preparation of carbon capture cement self-healing agent solution: Dimethylaminopropylamine was added to epoxy emulsion (so that the mass fraction of dimethylaminopropylamine in the epoxy emulsion was 25.0%), stirred at 400 rpm, and reacted at 60° C. for 4 h to obtain a carbon capture cement self-healing agent solution.

[0061] (3) Preparation of carbon capture cement self-healing agent: freeze-dry the carbon capture cement self-healing agent solution obtained in step (2) and grind it to obtain a dry carbon capture cement self-healing agent.

[0062] (4) The carbon capture cement self-healing agent, water, and G-grade oil well cement are prepared according to a water-cement ratio of 0.44 and a mass ratio of the carbon capture cement self-healing agent to G-grade oil well cement of 3:97, and are prepared according to GB / T 19139-2012 and cured in a curing box at 60°C±2°C for 7 days.

[0063] Figure 1 The scanning electron microscope image and X-ray energy spectrum analysis image of the carbon capture cement self-healing agent prepared in Example 1 in the cement matrix. Figure 1 As can be seen in (a), the polymer network structure of the carbon capture cement self-healing agent appears in the cement matrix; Figure 1 As shown in (b), the carbon capture cement self-healing agent has good compatibility with the cement matrix, among which the C element ( Figure 1 (c)) is mainly from carbon capture cement self-healing agent, O element ( Figure 1 (d) comes from the carbon capture cement self-healing agent and calcium hydroxide in the cement matrix, and the N element ( Figure 1 (e)) comes from the tertiary amine functional group of the carbon capture cement self-healing agent, the Ca element ( Figure 1 (f)) comes from the cement matrix.

[0064] Figure 2 This is a thermogravimetric test diagram of the carbon capture cement self-healing agent prepared in Example 1. Figure 2 From (b), it can be seen that the carbon capture cement self-healing agent mainly has two main thermal decomposition temperature ranges of 150-200℃ and 350-450℃. Figure 2As can be seen from (a), at 150-200°C, the weight loss rate is 4.31% due to the thermal decomposition of bicarbonate generated by the carbon capture cement self-healing agent capturing carbon dioxide in the air during the synthesis process; at 350-450°C, the weight loss rate is 74.33% due to the thermal decomposition of the carbon capture cement self-healing agent.

[0065] Figure 3 This is a carbon dioxide adsorption test diagram of the carbon capture cement self-healing agent prepared in Example 1. As can be seen from the figure, the carbon capture cement self-healing agent reaches the maximum carbon dioxide adsorption rate of 1.52mmolCO2 / g at 65min, has excellent carbon capture performance, and is conducive to accelerating the generation of cement matrix self-healing products.

[0066] Example 2

[0067] The only difference from Example 1 is that the mass ratio of carbon capture cement self-healing agent to G-grade oil well cement is 1:99; the remaining steps and parameters are the same as those in Example 1.

[0068] Example 3

[0069] The only difference from Example 1 is that the mass ratio of carbon capture cement self-healing agent to G-grade oil well cement is 6:94; the remaining steps and parameters are the same as those in Example 1.

[0070] Example 4

[0071] A method for preparing a carbon capture cement self-repairing agent, comprising the following steps:

[0072] (1) Preparation of epoxy emulsion: Mix water-based modified bisphenol F epoxy resin, Span-60 and water, and stir them evenly at 11000 rpm to obtain epoxy emulsion; the mass fraction of water-based modified bisphenol F epoxy resin in the epoxy emulsion is 55.0%; the mass fraction of Span-60 in the epoxy emulsion is 0.55%.

[0073] (2) Preparation of carbon capture cement self-healing agent solution: 4-dimethylaminobutylamine was added to epoxy emulsion (so that the mass fraction of 4-dimethylaminobutylamine in the epoxy emulsion was 27.5%), stirred at 450 rpm, and reacted at 70°C for 8 hours to obtain a carbon capture cement self-healing agent solution.

[0074] (3) Preparation of carbon capture cement self-healing agent: freeze-dry the carbon capture cement self-healing agent solution obtained in step (2) and grind it to obtain a dry carbon capture cement self-healing agent.

[0075] (4) The carbon capture cement self-healing agent, water, and G-grade oil well cement are prepared according to a water-cement ratio of 0.44 and a mass ratio of the carbon capture cement self-healing agent to G-grade oil well cement of 3:97, and are prepared according to GB / T 19139-2012 and cured in a curing box at 60°C±2°C for 7 days.

[0076] Example 5

[0077] A method for preparing a carbon capture cement self-repairing agent, comprising the following steps:

[0078] (1) Preparation of epoxy emulsion: Mix water-based modified bisphenol S epoxy resin, Span-85 and water, and stir them evenly at 12000 rpm to obtain epoxy emulsion; the mass fraction of water-based modified bisphenol A epoxy resin in the epoxy emulsion is 60.0%; the mass fraction of Span-80 in the epoxy emulsion is 0.6%.

[0079] (2) Preparation of carbon capture cement self-healing agent solution: Dimethylaminoethylamine was added to epoxy emulsion (so that the mass fraction of dimethylaminoethylamine in the epoxy emulsion was 30.0%), stirred at 500 rpm, and reacted at 80° C. for 10 h to obtain a carbon capture cement self-healing agent solution.

[0080] (3) Preparation of carbon capture cement self-healing agent: freeze-dry the carbon capture cement self-healing agent solution obtained in step (2) and grind it to obtain a dry carbon capture cement self-healing agent.

[0081] (4) The carbon capture cement self-healing agent, water, and G-grade oil well cement are prepared according to a water-cement ratio of 0.44 and a mass ratio of the carbon capture cement self-healing agent to G-grade oil well cement of 3:97, and are prepared according to GB / T 19139-2012 and cured in a curing box at 60°C±2°C for 7 days.

[0082] Comparison Example

[0083] Construction of blank cement system: Water and G-grade oil well cement were prepared at a water-cement ratio of 0.44, prepared according to GB / T19139-2012 and cured in a curing box at 60°C ± 2°C for 7 days.

[0084] Figure 4 The following are rheological test diagrams of cement matrices prepared in the control example, example 1, example 2, and example 3. Figure 4 It can be seen that the addition of carbon capture cement self-healing agent will not change the fluid properties of the cement matrix; with the increase of the addition amount of carbon capture cement self-healing agent, the consistency of the cement matrix decreases and the rheological properties of the cement matrix improve.

[0085] Figure 5 The hydration heat release test diagram of the cement matrix prepared in the control example, example 1, example 2 and example 3. Figure 5 It can be seen that the peak hydration exotherm rate of the blank cement system is 14.81 mW / g; with the increase in the amount of carbon capture cement self-healing agent added, the peak hydration exotherm rate of the cement matrix is ​​slightly delayed, which is because the polymer network structure of the carbon capture cement self-healing agent delays cement hydration; the peak hydration exotherm rate of the cement matrix first increases and then decreases with the increase in the amount of carbon capture cement self-healing agent added, and the peak hydration exotherm rate of Example 1 is the largest, which is 16.91 mW / g.

[0086] Figure 6 The super depth of field pictures and the repair rates of the cement matrix prepared in the control example and Example 1 before and after repair. Figure 6 From (d) to (f), it can be seen that after 3 or 7 days of repair at 60°C in a carbon dioxide environment, the 3-day self-repair rate of the control example is only 11.4%, and the 7-day self-repair rate is only 15.3%. Figure 6 From (a) to (c), it can be seen that the 3d self-repair rate of Example 1 reaches 49.8%, and the 7d self-repair rate reaches 94.3%, with an increase of 516.3%. This is because the carbon capture cement self-repair agent accelerates the absorption of carbon dioxide by the cement matrix, promotes the generation of self-repair products, and greatly improves the self-repair ability.

[0087] The cement matrix prepared in Examples 2-5 was subjected to a self-healing performance test, and the test results were similar to those in Example 1. The results showed that the carbon capture cement self-healing agent prepared by the present invention had excellent carbon capture performance, had little effect on the hydration of the cement matrix, and greatly improved the rheological properties and self-healing performance of the cement matrix.

[0088] In summary, the carbon capture cement self-healing agent of the present invention has a simple preparation process, is easy to realize industrial production, has little effect on cement hydration, is beneficial to improving the rheological properties of cement, and effectively solves the shortcomings of traditional cement self-healing systems that are difficult to industrialize and have slow self-healing speed.

[0089] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a carbon capture cement self-repairing agent, characterized in that: The following steps are involved: Evenly mixing water-based epoxy resin, surfactant and water to obtain epoxy emulsion; Adding a tertiary amine curing agent to the epoxy emulsion for reaction to obtain a carbon capture cement self-healing agent solution; The carbon capture cement self-repairing agent solution is freeze-dried and then ground to obtain the carbon capture cement self-repairing agent.

2. The method for preparing the carbon capture cement self-repairing agent according to claim 1, characterized in that: The mass fraction of the waterborne epoxy resin in the epoxy emulsion is 50.0%-60.0%; the mass fraction of the surfactant in the epoxy emulsion is 0.5%-0.6%.

3. The method for preparing the carbon capture cement self-repairing agent according to claim 1, characterized in that: The waterborne epoxy resin is waterborne modified bisphenol A epoxy resin, waterborne modified bisphenol F epoxy resin or waterborne modified bisphenol S epoxy resin; the epoxy value of the waterborne epoxy resin is 0.41-0.51, and the average dispersed particle size in water is 4-8 μm; the surfactant is Span-80, Span-60 or Span-85.

4. The method for preparing the carbon capture cement self-repairing agent according to claim 1, characterized in that: The mass fraction of the tertiary amine curing agent in the epoxy emulsion is 25.0%-30.0%.

5. The method for preparing the carbon capture cement self-repairing agent according to claim 1, characterized in that: The tertiary amine curing agent is dimethylaminopropylamine, 4-dimethylaminobutylamine or dimethylaminoethylamine.

6. The method for preparing the carbon capture cement self-repairing agent according to claim 1, characterized in that: The reaction temperature is 60-80°C and the reaction time is 4-10h.

7. A carbon capture cement self-healing agent prepared according to the preparation method according to any one of claims 1 to 6.

8. Use of the carbon capture cement self-repairing agent as claimed in claim 7 in the self-repair of cement ring of cementing.

9. A self-repairing cement-based material, characterized in that: The raw materials include the carbon capture cement self-repairing agent according to claim 7 and cement.

10. The self-repairing cement-based material according to claim 9, characterized in that: The mass ratio of the carbon capture cement self-healing agent to the cement is (1-6):(99-94).